KINERJA APARATUR DALAM MENINGKATKAN KUALITAS PELAYANAN DI BADAN PENGHUBUNG PEMERINTAH PROVINSI KALIMANTAN TENGAH DI JAKARTA - Ichsan Fravidya Nugraha; Khasan Effendy; Dahyar Daraba (GoAcademica Research dan Publishing, 2021)
This study was aimed to investigate the performance of the workers of the Liaison Agency of the Central Kalimantan Provincial Government in delivering their services. This study employed the qualitative method with descriptive analysis. Data used in this studywere obtained through interview, observation, and document analysis. This study examined the performance of the workers in improving the quality of service and focused on the mechanism and strategy that the workers used in conducting their duties andidentification of the factors that affecting their performance. Then, all the datawere analyzed using the SWOT method and Litmust Test. The result of this study shows that the performance of the workers of the Liaison Agency of the Central Kalimantan Provincial Government is not optimal. Some of the difficulties that are found to be the reasons of the dissatisfied performance of the workers are the low level of education and knowledge and the lack of experience. Furthermore, there is only a few numbers of workers that have the technical capability, limited opportunity to improve their capability through education or training either in structural or functional form, and the limited chance to pursue higher education that caused the poor quality of service.